Studies of the Physicochemical Properties, Stability, Irritability, and Efficacy of Red Boroco (Celosia argentea) Leaf Extract Patch for Diabetic Wound Healing - Siti Fatmawati Fatimah; Nurul Safira Basuki; Nuri Ari Efiana (Borneo Journal of Pharmacy, 2026)
Red Boroco (Celosia argentea) leaves contain flavonoids that act as wound healers by promoting skin tissue repair and fibroblast growth. The 15% w/w C. argentea leaves extract was formulated into a patch for diabetic wound healing. This study aims to evaluate the physicochemical characteristics, physical stability, irritability, and efficacy of the C. argentea leaves extract patch for diabetic wound healing. Celosia argentea leaves were macerated in 70% ethanol, the flavonoid content was measured, and the extract was formulated into a patch. Evaluation of the patch included measurements of organoleptic properties, pH, weight uniformity, folding resistance, patch thickness, moisture content, and moisture uptake. A stability study was conducted using a freeze-thaw cycle method. The Hen's Egg Test-Chorioallantoic Membrane (HET-CAM) to confirm the irritability of the patch. The efficacy study was conducted by measuring the percentage of wound closure in male Wistar rats. The results showed that C. argentea leaves contained 1.101 ± 0.012 μg QE of flavonoids. The patch characteristics were as follows: pH 6.16 ± 0.01; weight uniformity 0.513 ± 0.038 g; folding resistance >300 folds; patch thickness 0.4 mm; moisture content 0.031 ± 0.028%; and moisture uptake 0.030 ± 0.009%. Statistical analysis (unpaired t-test) showed no significant changes in physical properties after the freeze–thaw cycle (p >0.05), indicating good stability. The one-way ANOVA test of wound closure showed no significant difference between the patch group and the positive control group (p = 0.948). Patch exhibited good physical stability, no irritation, and an 89.88% wound-healing rate in the test animal.